Relative retentivity of knowledge in fish processing by fisherwomen - Kandoran, M.K., Thiagarajan, R. and (Fishery Technology, 2021)
Retention of knowledge in the preparation of fish pickle, fish wafers and fish soup powder for an experimental group of 20 fisherwomen selected from three fishing villages was studied. The knowledge retention immediately after exposure and also at intervals of 15 days and 30 days after exposure differed significantly.